2019
DOI: 10.1523/jneurosci.1153-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

The Functional Role of Thalamocortical Coupling in the Human Motor Network

Abstract: The amplitude of high broadband activity in human cortical field potentials indicates local processing and has repeatedly been shown to reflect motor control in the primary motor cortex. In a group of male and female subjects affected by essential tremor and undergoing deep brain stimulation surgery, ventral intermediate nucleus low-frequency oscillations (Ͻ30 Hz) entrain the corticomotor high broadband activity (Ͼ40 Hz) during rest, relinquishing that role during movement execution. This finding suggests that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 65 publications
5
22
0
Order By: Relevance
“…The potential for neural coprocessors is being explored in several ongoing investigational human studies. For example, the Activa™ PC+S system has been used to create novel thalamocortical circuit connections in patients with essential tremor, Tourette’s, and Parkinson's disease as part of the NIH BRAIN initiative [8], [9], [10]. To help illustrate the elements of a neural coprocessing system, we will analyze an adaptive deep brain stimulation example from essential tremor.…”
Section: Design Inputs For a Neural Coprocessormentioning
confidence: 99%
See 1 more Smart Citation
“…The potential for neural coprocessors is being explored in several ongoing investigational human studies. For example, the Activa™ PC+S system has been used to create novel thalamocortical circuit connections in patients with essential tremor, Tourette’s, and Parkinson's disease as part of the NIH BRAIN initiative [8], [9], [10]. To help illustrate the elements of a neural coprocessing system, we will analyze an adaptive deep brain stimulation example from essential tremor.…”
Section: Design Inputs For a Neural Coprocessormentioning
confidence: 99%
“…Fully embedded cortical sensing movement-related beta desynchronization being utilized to control sub-cortical thalamic stimulation in an essential tremor subject. Note that as the patient moves (highlighted in green), the low frequency signals desynchronize around 20Hz, and the stimulation amplitude increases [9].…”
Section: Figurementioning
confidence: 99%
“…Similarly, a strong PAC between the depth electrode (phase) and the subdural strip (amplitude) was observed ( Figure 2B). Malekmohammadi et al [13] and our group have both shown the presence of PAC between the VIM and M1 [19]. This PAC was not a feature observed in the three other TS patients recruited into the study.…”
Section: Resultsmentioning
confidence: 44%
“…Cross-frequency coupling has also been observed between the gamma activity from the M1 and the low-frequency oscillations from the ventral intermediate nucleus (i.e. the motor nucleus of the thalamus) (38). Thalamo-cortical PAC has been suggested to play a role as a mechanism for gating motor behavior.…”
Section: Motor-related Phase-amplitude Couplingmentioning
confidence: 98%